Resident perceptions of sustainable tourism development: Frankenwald Nature Park, Germany. (20th July 2010) - Huayhuaca, Ch'aska; Cottrell, Stuart; Raadik, Jana; Gradl, Sabine
This paper examined the relationship between four dimensions of sustainability and perceptions of tourism development held by residents of communities in and around Frankenwald Nature Park (FNP) in central Germany (n = 306). Building on a previous study (Shen and Cottrell, 2008), it was hypothesised that ratings for the ecological, economic, institutional and socio-cultural dimensions of sustainability would contribute to resident satisfaction. Final dimensional indices consisted of 5-9 survey items with reliability coefficients ranging from 0.63 to 0.87. Regression analyses revealed all four dimensions of sustainability as significant predictors of resident satisfaction with tourism to FNP. The theoretical and applied implications of these findings for understanding tourism sustainability are discussed.